Barriers to being seen: the interpersonal experiences of AFAB University students with ADHD in South Africa - Malefane, Reitumetse (Department of Psychology, 2025)
Adults who were assigned female at birth (AFAB) are an under-represented group in ADHD literature and little is known about their lived experiences. This study aimed to explore how AFAB university students with ADHD experience interpersonal relationships. Using an interpretive phenomenological framework, 12 AFAB students from a South African university were recruited to participate in individual semi-structured interviews. Reflexive thematic analysis was employed to synthesise the data and generate a narrative account of the following two overarching themes, ‘compromised connection and vulnerability' and ‘strategising to find connection'. The findings depicted that the participants' interpersonal experiences were marked by frequent invalidation, judgement, and misunderstanding from those in their life. These factors were described as barriers to experiencing close and fulfilling interpersonal relationships. However, the participants also described several strategies that they believed buffered their negative social experiences. Whilst these strategies were shown to limit conflict and alienation, several of them were also demonstrated to be exhausting and detrimental to the participants' overall wellbeing. As such, this study highlighted the importance of mutually accommodating and supportive interpersonal relationships for AFAB adults with ADHD.